1977
DOI: 10.1002/ardp.19773100608
|View full text |Cite
|
Sign up to set email alerts
|

Utility of π‐Acceptors in Alkaloid Assay

Abstract: The interaction of alkaloids with selected polyhaloquinone and polycyanoquinone n-acceptors was found to yield intensely coloured radical ions. This finding was developed into a sensitive spectrophotometric assay for alkaloids of general applicability and with adequate accuracy and precision. 7,7,8,8-Tetracyanoquinodimethane is used as the reagent. Anwendung von rr-Acceptoren zur quantitativen Analyse von AlkaloidenAkaloide geben mit rr-Acceptoren vom Typ der Polyhalogenchinone und Polycyanochinone intensiv ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…The dissociation of the (D-A) complex was promoted by the high ionizing power of the polar solvent and the resulting peaks in the absorption spectra of D-acceptor reaction mixtures were similar to the maxima of the radical anions of the acceptors obtained by the iodide reduction method [22].…”
Section: Spectral Characteristics Of the Reactionmentioning
confidence: 61%
See 1 more Smart Citation
“…The dissociation of the (D-A) complex was promoted by the high ionizing power of the polar solvent and the resulting peaks in the absorption spectra of D-acceptor reaction mixtures were similar to the maxima of the radical anions of the acceptors obtained by the iodide reduction method [22].…”
Section: Spectral Characteristics Of the Reactionmentioning
confidence: 61%
“…Polar solvents such as acetonitrile and alcohols were found to be unsuitable as their blanks with iodine gave high absorbance. It is obvious that, the rate of transformation of the outer complex to inner complex is in the order of 1,2-dichloroethane > dichloromethane > chloroform [22]. There is actually a considerable decrease in the energy of activation along with an increased dielectric constant ε r of the medium; in 1,2-dichloroehane (ε r = 10.2) the transformation of inner complex proceeds much faster than that in dichloromethane (ε r = 9.1) and chloroform (ε r = 4.8).…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 99%
“…Dissociation of the (D-A) complex was promoted by the high ionizing power of the polar solvent and the resulting peaks in the absorption spectra of drug-acceptor reaction mixtures were similar to the maxima of radical anions of the acceptors obtained by the iodide reduction method (15). …”
Section: Reaction and Spectral Characteristicsmentioning
confidence: 62%
“…Further support to this assignment was provided by the absorption maxima with those of the DDQ radical anion produced by the iodide reduction method (15). Dissociation of the (D-A) complex was promoted by the high ionizing power of the polar solvent and the resulting peaks in the absorption spectra of drug-acceptor reaction mixtures were similar to the maxima of radical anions of the acceptors obtained by the iodide reduction method (15).…”
Section: Reaction and Spectral Characteristicsmentioning
confidence: 86%
“…2). This band was attributed to the formation of the radical anion DDQ - (21), which was probably formed by the dissociation of an original donor-acceptor (D-A) complex: (19) demonstrated that the interaction of electron donors with DDQ in polar solvents (e.g., methanol and acetonitrile) produced CT complexes with molar absorptivity values higher than those produced in non-polar sol- vents (e.g., chloroform). Different polar solvents were tested to prepare the DDQ solution: methanol, ethanol, 1-propanol, 1-butanol, and acetonitrile.…”
Section: Reaction and Spectral Characteristicsmentioning
confidence: 99%